Association between Physical Literacy and Physical Activity: A Multilevel Analysis Study among Chinese Undergraduates - Ma, Rui-Si (Int J Environ Res Public Health, 2020)
Aim: To examine the association between the perceived physical literacy (PL) and physical activity (PA) levels among Chinese undergraduates. Methods: Simplified Chinese version of the Perceived Physical Literacy Instrument and the International Physical Activity Questionnaire were used to measure 536 students’ perceived PL and PA levels. Pearson’s product-moment correlation and multiple linear regression were then used to examine the relationship between the perceived PL and PA levels. Additionally, standard regression analysis was conducted to test for the effects at different demographics. Results: The correlation between perceived PL and PA level was low but significant (r = 0.350, p < 0.01). The multiple linear regression equation was significant (F = 25.228, p < 0.01, ΔR(2) = 0.120). Metabolic equivalent values were used to predict PA levels of participants, which were −3818.582 + 272.535 (motivation) + 249.848 (confidence and physical competence) + 149.899 (interaction with the environment). The association of factors such as socio-economic status (SES) (p = 0.092) and grade point average (GPA) (r = 0.119, p = 0.022) were examined using Pearson’s product-moment correlation. Gender (p < 0.01) and body mass index (BMI) (p < 0.01) were also explored for their differences. Conclusions: Perceived PL and PA levels were significantly related. The association between PL and GPA was identical. GPA and BMI showed significant difference between each group. The study offers a path to explore the concept of PL and how it can affect the PA of Chinese undergraduates. Furthermore, on the basis of this study, more research could develop practical interventions for Chinese undergraduates to enhance their PL and engagement in a lifetime of PA.